Perservation of heritage or integration for survival: The case of a Chinese mother in Japan - Saito, Hiroki (Journal of Modern Languages, 2025)
The study aims at exploring a contested ideology toward heritage language maintenance and social integration based on a one-on-one interview to a Chinese mother in Japan. Through the framework of Family Language Policy, semi-structured interview data were analyzed thematically in terms of language ideology, practice, and maintenance. Findings show that a Chinese mother who raises a daughter in Japan struggles to balance bilingual education between Chinese and Japanese to pass down the former language for heritage maintenance and simultaneously teach the latter language for the successful integration to the destination country. I end this article by providing recommendations for migrant language education in Japan.